2010
DOI: 10.1093/nar/gkq845
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal domain of archaeal O -phosphoseryl-tRNA kinase displays large-scale motion to bind the 7-bp D-stem of archaeal tRNA Sec

Abstract: O-Phosphoseryl-tRNA kinase (PSTK) is the key enzyme in recruiting selenocysteine (Sec) to the genetic code of archaea and eukaryotes. The enzyme phosphorylates Ser-tRNASec to produce O-phosphoseryl-tRNASec (Sep-tRNASec) that is then converted to Sec-tRNASec by Sep-tRNA:Sec-tRNA synthase. Earlier we reported the structure of the Methanocaldococcus jannaschii PSTK (MjPSTK) complexed with AMPPNP. This study presents the crystal structure (at 2.4-Å resolution) of MjPSTK complexed with an anticodon-stem/loop trunca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 24 publications
5
22
0
Order By: Relevance
“…Similar base stacking of the nucleotide at position 9 is also observed in the eukaryal/archaeal tRNA Sec s (Figure 4F–I) (10,11,14). U9 of human tRNA Sec is only stacked on the A48 base of the G45:A48 pair, while A9 of the archaeal tRNA Sec s is stacked on the interbase hydrogen-bonding region of the base pair G45:C48.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Similar base stacking of the nucleotide at position 9 is also observed in the eukaryal/archaeal tRNA Sec s (Figure 4F–I) (10,11,14). U9 of human tRNA Sec is only stacked on the A48 base of the G45:A48 pair, while A9 of the archaeal tRNA Sec s is stacked on the interbase hydrogen-bonding region of the base pair G45:C48.…”
Section: Resultssupporting
confidence: 72%
“…The asymmetric unit contains two tRNA Sec molecules (chains C and D) and one PSTK dimer, and the A9s in chains C and D adopt different ribose puckering modes, C3′-endo and C2′-endo, respectively (G and H). The C2′-endo puckering is assumed by the U9s of the A. aeolicus (E) and human (F) tRNA Sec s. On the other hand, the asymmetric unit of the M. jannaschii tRNA Sec •PSTK co-crystal contains one tRNA Sec molecule and one-half of a PSTK dimer [PDB ID: 3AM1 (14)], and the A9 ribose puckering is C2′-endo (I). C8 and U8 of the M. kandleri and M. jannaschii tRNA Sec s, respectively, are further stacked on A9.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A mutated human tRNA Sec with a fourbase-pair D-loop showed decreased PSTK phosphorylation when compared with the wild type with a six-base-pair Dloop [22], and recent data demonstrated that identification of tRNA Sec in archaea is dependent on the D-loop structure [23]. Moreover, the Kinetoplastidae tRNA Sec has a 7/5 structure in the acceptor-T C stem, with seven nucleotides in the acceptor stem and five nucleotides in the T C stem, while the human [24] and the archaea [25] tRNA Sec have a 9/4 structure. These structural differences in the tRNA Sec of Kinetoplastidae suggest an equivalent adaptive modification in the enzymes that interact with and recognize such tRNAs, including the ribosome A site.…”
Section: Specific Characteristics Of Kinetoplas-tid Selenocysteine Bimentioning
confidence: 96%